1994
DOI: 10.1002/chir.530060709
|View full text |Cite
|
Sign up to set email alerts
|

Chiral lumazines: Preparation, properties, enantiomeric separation

Abstract: Optically active lumazines (biolumazine, dictyolumazine, monalumazine, and neolumazine) are prepared from the corresponding pterins by enzymatic reaction, using pterin deaminase excreted by Dictyostelium discoideum. The fluorescence properties, circular dichroism spectra, and chromatographic behavior of these lumazines are studied. D- and L-enantiomers of biolumazine, dictyolumazine, and monalumazine are separated using a chiral flavoprotein column. This column also separates the enantiomeric pterins of the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This process is controlled by cAMP, whose signal transduction is linked to heterotrimeric G-proteins [10,11]. Recently, we have shown that tetrahydrodictyopterin [12,13], the threo-isomer of BH % , originates from GTP by de no o biosynthesis requiring the action of GTP-CH [14]. During the developmental process the activity of GTP-CH is regulated independently in the cytosolic and membrane fractions.…”
Section: Introductionmentioning
confidence: 99%
“…This process is controlled by cAMP, whose signal transduction is linked to heterotrimeric G-proteins [10,11]. Recently, we have shown that tetrahydrodictyopterin [12,13], the threo-isomer of BH % , originates from GTP by de no o biosynthesis requiring the action of GTP-CH [14]. During the developmental process the activity of GTP-CH is regulated independently in the cytosolic and membrane fractions.…”
Section: Introductionmentioning
confidence: 99%
“…30 Dictyolumazine (38) was observed in the media of starved Dictyostelium discoideum and identified by comparison to a semisynthetic chiral standard using chiral HPLC. 64,65 Dictyolumazine (38) was demonstrated to be responsible for the extracellular fluorescence linked with the aggregation ability of D. discoideum cells. 64 No other biological properties were reported for chiral lumazines 34−38.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
“…The 1′ S ,2′ R -configuration of dihydroxylumazine 37 was determined by diacetylation of the compound and comparison of its spectroscopic data with those of a semisynthetic sample . Dictyolumazine ( 38 ) was observed in the media of starved Dictyostelium discoideum and identified by comparison to a semisynthetic chiral standard using chiral HPLC. , Dictyolumazine ( 38 ) was demonstrated to be responsible for the extracellular fluorescence linked with the aggregation ability of D. discoideum cells . No other biological properties were reported for chiral lumazines 34 – 38 .…”
Section: -Substituted Lumazinesmentioning
confidence: 99%
“…It was named dictyopterin and represents a new naturally occurring isomer of -biopterin [28]. It was also shown that dictyopterin is deaminated by an extracellular pterin deaminase to -threo-1,2-dihydroxypropyl lumazine (-dictyolumazine) [29].…”
Section: Introductionmentioning
confidence: 99%